Effect of bottle gourd leaf (Lagenaria siceraria) extract on the quality of beef meatball: Bottle gourd leaf extract on meatball (Bangladesh Journal of Animal Science, 2018)
The experiment was conducted to find out the effect of different levels of bottle gourd leaf extraction on beef meatballs. Ground beef samples were divided into four treatment groups having bottle gourd leaf extracts as control T1 (0%), T2 (1%), T3 (2%), T4 (3%). Proximate analysis, sensory tests (color, flavor, tenderness, juiciness, and overall acceptability), cooking loss, pH value, free fatty acids (FFA), thiobarbituric acid values (TBARS), peroxide value (POV) and microbiological examination were determined. Days of intervals of experiment were 0, 15th, 30th and 45th days. Data were analyzed using SAS Statistical software. DM content of all the treatment groups differ significantly (p